Prototype Aplikasi Marketplace Hewan - Oktavian, Karel; Ikhsani, Iqbal Nur; Susanto, Fredy; Ryando, M. Bucci (Universitas Batanghari Jambi, 2025)
Nowadays, trading through marketplaces has become a part of everyday life. Names like Tokopedia, Shopee, and Bukalapak are no longer unfamiliar to the public. This Animal Marketplace Application prototype was created as a platform where animal sellers and buyers can meet. Typically, animal trading is done offline by visiting the seller's location. However, it is very difficult to find animal sellers due to its complex segmentation. Cloud-based and using a mobile platform, the animal marketplace is designed to connect sellers and buyers from various locations, aiming to facilitate interactions between them. The hope is that this application can help small and medium enterprises (SMEs) in Indonesia.